1990
DOI: 10.3758/bf03334073
|View full text |Cite
|
Sign up to set email alerts
|

The effects of irrelevant speech on immediate free recall

Abstract: Immediate ordered recall is strongly disrupted by concurrent irrelevant speech even when the speech is unfamiliar to the subject. This effect has been replicated in many experiments with immediate serial recall. In the present study, we examined the effect of speech on immediate free recall of lists of 16 words presented visually. No impairment in the speech condition was found in comparison with the control, but the same subjects showed a consistent impairment of immediate serial recall under speech in a sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 14 publications
(15 reference statements)
3
57
1
Order By: Relevance
“…The results of the present experiments contrast with those of Salamé and Baddeley (1990), who observed no ISE in a free recall task. The results of Experiment 1 do replicate LeCompte's (1994) findings of an ISE using several nonserial recognition paradigms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The results of the present experiments contrast with those of Salamé and Baddeley (1990), who observed no ISE in a free recall task. The results of Experiment 1 do replicate LeCompte's (1994) findings of an ISE using several nonserial recognition paradigms.…”
Section: Discussioncontrasting
confidence: 56%
“…A handful of studies have addressed this issue by examining the ISE in free recall or recognition tasks. The first test of whether or not serial rehearsal is required for observing the ISE came from Salamé and Baddeley (1990), who examined the effect of irrelevant speech in an immediate free recall paradigm. Participants did not show an ISE when they were permitted to report 16-item visual word lists in any order they wished.…”
Section: Introductionmentioning
confidence: 99%
“…So, for example, if the subject is given a list from a fixed set (such as days of the week) from which an item is missing and is then required to report the missing item, there is no effect of irrelevant speech (D. M. Jones & Macken, 1993;. Similarly, Salame and Baddeley (1990) found no irrelevant speech effects with free recall. Also, Morris and D. M. Jones (1990a) demonstrated that memory for the position of dots was not disrupted by irrelevant speech, a fmding that can be accommodatedby supposing that spatial material is stored on a visuospatial scratch pad rather than in phonological working memory.…”
Section: Is the Effect One Of Distraction?mentioning
confidence: 92%
“…In this case, the competition between pointers is minimized, which in turn accounts for the minimal disruptive effect on serial recall caused by irrelevant streams consisting of one repeated item. We therefore expect the disruption by irrelevant speech to be confined to serial recall and absent from tasks that demand free recall (D. M. Jones & Macken, 1993;Salame & Baddeley, 1990).…”
mentioning
confidence: 99%
“…This phenomenon, assumed to be modulated by the interference between the obligatory processing of order in the irrelevant sound and the deliberate seriation processing involved in the focal task (e.g., Jones & Macken, 1993;Jones & Tremblay, 2000;Marsh et al, 2009), typically disappears when the focal task does not encourage serial rehearsal (e.g., Beaman & Jones, 1997;Hughes et al, 2007;Marsh, Hughes, & Jones, 2008;Salamé & Baddeley, 1990).…”
Section: Implications For the Understanding Of Auditory Attentional Cmentioning
confidence: 99%